UMRAH MARKETING MANAGEMENT: ATTRACTING THE INTEREST OF MILLENNIAL PILGRIMAGES - Mohammad Zainullah (IZZI: Jurnal Ekonomi Islam, 2026)
This study aims to analyze the implementation of Sharia-based digital marketing innovation in increasing millennial pilgrims’ interest at PT Nurul Haramain Mulia. The research employed a descriptive qualitative approach with a case study design. Data were collected through semi-structured interviews, observation of the company’s social media platforms, and internal documentation, and were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that the implementation of digital marketing strategies through social media, online registration and payment systems, and inspirational educational content increased millennial pilgrims’ interest by approximately 35% among those aged 25–35. Furthermore, the application of Sharia marketing principles such as honesty, trustworthiness, and transparency strengthened customer trust and loyalty. The synergy between digital innovation and Islamic values has proven to be the key factor in the company’s success in attracting and retaining millennial pilgrims in the modern era.